Analysis of Mudharabah Agreements Fiqh Perspective on BMT UGT Nusantara - Nurul Laili; Rossa Nurmala (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Abstract Islamic Banks as intermediary institutions that operate based on Sharia principles must adjust all their products in accordance with the provisions of Islamic jurisprudence (fiqh) to ensure that every activity conducted by the bank is correct and does not violate Sharia regulations. Once an Islamic bank has aligned all aspects of its activities with Sharia provisions, it can conduct its banking operations correctly and appropriately, including engaging in cooperative agreements with customers. One of the contracts used in Islamic banking is the mudharabah contract. This research aims to assess the application of the mudharabah contract at BMT UGT NUSANTARA from a fiqh perspective. The research approach is descriptive-analysis, a qualitative method that guides researchers to explore and thoroughly examine the situation under study. Data collection techniques include observation and interviews. The expected outcome of this study is to provide a comprehensive overview of the application of the mudharabah contract in Islamic banking from a fiqh perspective based on field research.